Interactive user interface for food ordering system using QR code technology - Chai, Wei Ching (2014)
Interactive User Interface for Food Ordering System using QR Code Technology is a real time ordering system to manage the order process for restaurant. The current system is using traditional way which is paper menu and using paper sheets to record the orders of customers. They do not have a proper ordering system to support and make the ordering process smoothly. Nowadays, smartphone and tablet have widely used in our daily life. Therefore, this system is developed to provide an electronic ordering system using mobile and tablet for customers in order to increase the restaurant productivity. There are two target users which are restaurant customers and restaurant administrator. This system is divides into three subsystems which are Android-based and Web-based Food Ordering System and Administrator Management System. Besides, QR code is used to encode the order details then will be decode by the tablet. This proposed system is using waterfall model as the methodology. There are five phases such as requirement phase, design phase, implementation phase, verification phase and maintenance phase.